Initial Coin Offering (ICO): the Case of Ukraine - I. Lyutyy (Vìsnik. Kiïvsʹkogo Nacìonalʹnogo Unìversitetu ìmenì Tarasa Ševčenka. Ekonomìka, 1899)
It is emphasized that the Ukrainian corporate sector may use ICOs for financing its activities quite successfully provided that ICO is supported by the state and the national legislation for it is created and implemented.